THE DIFFERENCE OF MAP1LC3 LEVEL AS MACROPHAGE AUTOPHAGY MARKER BETWEEN RESISTANT AND SENSITIVE TUBERCULOSIS PATIENTS ON RIFAMPICIN - Wulandari, Dian Novita; Nugraha, Jusak; Soedarsono, Soedarsono (Institute of Topical Disease Universitas Airlangga, 2018)
M. tuberculosis (MTB) is an intracelular bacteria that live in the host macrophage cells. Several organs can be affected by tuberculosis but most major illnesses are lung diseases. Immediately after infection, MTB will be phagocytosed by the alveolar macrophage cells and can survive in the phagosome. The macrophage plays a role in innate immunity towards an infection using autophagy by removing the microbe directly via phagocytosis. When bacteria phagocytosized, vacuole membrane formed double membranes called autophagosome, and followed by degradation by lysosome, which known as autolysosome. Induction of autophagy can be observed on the formation of microtubule-associated proteins 1B lightchain 3B (MAP1LC3B/LC3). MAP1LC3B is protein that have role at autophagic way for selection autophagy substrate and biogenesis. In this study we are used serum from patients TB with rifampicin resistant and rifampicin sensitive as control. Samples were divided using gene expert to differentiate between resistant and sensitive rifampicin.This research aims to compare MAP1LC3B levels in resistant and sensitive rifampicin to study macrophages respond in autophagic way in tuberculosis patients, and give information for define therapy plan to improve therapy for MDR-TB patients. Type of this research is a case control study design with cross sectional research with each groups sample is 19 from age 18-65 years old. Result, MAP1LC3B serum levels on the rifampicin resistant group are lower compared to rifampicin sensitive group. This occur because MTB is able to hide and evade innate immune defense mechanisms. MTB can maintain intracellular growth inside the phagosome by inhibiting phagolysosome formation in autophagy process especially inhibit MAP1LC3B formation by PDIM.